Effects of intrauterine growth restriction and female sex on future blood pressure and cardiovascular disease - Davis, Gwendolyn K (Curr Hypertens Rep, 2017)
PURPOSE OF THE REVIEW: It is well-established that the age-related increase in blood pressure is augmented after menopause. Yet, the prevalence of hypertension is enhanced in low birth weight women relative to normal birth weight counterparts by 60 years of age suggesting that adverse influences during fetal life heighten cardiovascular risk in later life. RECENT FINDINGS: A changing hormonal milieu may contribute to increased cardiovascular risk that occurs after the menopausal transition. Low birth weight is associated with early age at menopause. A recent study indicates that a shift towards testosterone excess following early reproductive senescence may contribute to the etiology of age-dependent increases in blood pressure in a rodent model of low birth weight. SUMMARY: This review will highlight current findings related to postmenopausal hypertension and discuss potential mechanisms that may contribute to the enhanced cardiovascular risk that develops with age in low birth weight women.